Contact System Activation and Cancer: New Insights in the Pathophysiology of Cancer-Associated Thrombosis - Campello, E.; Henderson, M.W.; Noubouossie, D.F.; Simioni, P.; Key, N.S. (Thrombosis and Haemostasis, 2018)
Cancer induces a systemic hypercoagulable state that elevates the baseline thrombotic risk of affected patients. This hypercoagulable state reflects a complex interplay between cancer cells and host cells and the coagulation system as part of the host response to cancer. Although the tissue factor (TF)/factor VIIa pathway is proposed to be the principal initiator of fibrin formation in cancer patients, clinical studies have not shown a consistent relationship between circulating TF levels (often measured as plasma microvesicle-associated TF) and the risk of thrombosis. A renewed interest in the role of the contact pathway in thrombosis has evolved over the past decade, raising the question of its role in the pathogenesis of thrombotic complications in cancer. Recent observations have documented the presence of activation of the contact system in gastrointestinal, lung, breast and prostate cancers. Although the assays used to measure contact activation differ, and despite the absence of standardization of methodologies, it is clear that both the intrinsic and extrinsic pathways may be activated in cancer. This review will focus on recent findings concerning the role of activation of the contact system in cancer-associated hypercoagulability and thrombosis. An improved understanding of the pathophysiology of these mechanisms may lead to personalized antithrombotic protocols with improved efficacy and safety compared with currently available therapies.
Keywords: contact activation; cancer; hypercoagulability; intrinsic pathway; thrombosis